Pengembangan Sistem Informasi Service Desk Berbasis Web Menggunakan UML dalam Mendukung Manajemen Tiket IT Support - depa mulyadi; Elin Rosliani (Masoem University, 2026)
This study aims to develop a web-based service desk information system to improve the effectiveness of IT support ticket management. The background of this research is the existing report handling process, which is still carried out manually. This condition often leads to several issues, such as poorly recorded data, duplicate reports, and difficulties in monitoring the problem resolution process. The system is designed using Unified Modeling Language (UML) to clearly represent system requirements and workflows. The development process follows the waterfall method, which consists of requirements analysis, system design, implementation, and testing stages. The developed system includes several main features, such as user authentication, ticket management, technician assignment, and real-time ticket status monitoring. With this system, data recording becomes more organized, and coordination between users, administrators, and technicians can be improved. Based on the testing results, the system shows improvements in work efficiency and makes it easier to monitor the problem-handling process. In addition, it helps reduce errors that commonly occur in manual processes. Therefore, this system can be used as a solution to improve the quality of IT support services in a more structured way.